LEGAL REGULATION ANALYSIS OF MEDICAL CARE PROVISION TO PATIENTS WITH ONCOLOGICAL PATHOLOGY TO RESIDENTS OF VARIOUS AGES, GENDER AND OCCUPATIONAL GROUPS IN THE RUSSIAN FEDERATION (Journal of Pharmaceutical Negative Results, 2023)
The recognized relevance of combating malignant neoplasms has necessitated the implementation of a unique nationwide program to combat oncological diseases in the Russian Federation and the construction of a modern integrated system, from screening and early diagnosis to timely effective treatment, which will protect a person.